Experience of living with pain among older adults with arthritis: A systematic review and meta-synthesis. (November 2020) - Chen, Jie; Hu, Fen; Yang, Bing Xiang; Cai, Yi; Cong, Xiaomei
Abstract: Background: Millions of people older than 60 years are affected by arthritis. Unrelieved chronic pain of arthritis is associated with increased healthcare needs and decreased quality of life in older adults. Understanding older adults' perceptions and experiences of living with arthritis pain can benefit healthcare experts in designing and implementing clinical, education, and research programs to better care for this population. Objectives: This meta-synthesis of qualitative studies aimed to explore older adults' experiences of living with arthritis pain. Design: A narrative meta-synthesis. Data sources/review method: Journal articles published in English were identified by conducting electronic searches in CINAHL, PubMed, PsycINFO, Scopus, and ISI Web of Science to June 2019. Unpublished studies were searched in Google Scholar, ProQuest Dissertations and Theses Database. Four groups of keywords were combined in the search strategy: (1) research methods/qualitative researches; (2) older adults; (3) arthritis/arthritis pain; (4) experience. Studies were included if they (a) used qualitative research designs, qualitative data collection and analysis; (b) included participants aged 60 years and older regardless of the study context; (c) reported on older adults' experiences of living with arthritis pain; and (d) were published in English. Studies were excluded if: (a) they used mixed methods where qualitative data could not be extracted or (b) the data analysis lacked the necessary qualitative depth. Noblit and Hare's methodology of synthesizing qualitative studies was used. Results: Eleven studies were included. Among the 11 included studies published in 2003–2018, the sample size ranged from 3 to 551 participants. Older adults aged 62 to 95 years, and the majority were female. The ethnicity of the older adults was reported in 7 studies, including Caucasians, African Americans, Hispanics, Korean Americans, Australian, European, and South Korean. Through meta-synthesis, four themes were identified. The lived experiences of pain among older adults with arthritis include the center of daily living, a lonely path, an inevitable and endless process, and surviving through pain management. Conclusions: These themes may reflect older adults' experiences of living with arthritis pain across diverse ethnicities and cultures. Health care providers must be sensitive to older adults' experience of arthritis pain, realize the importance of providers' support on patients' adaptation, and provide comprehensive and individualized patient-centered interventions for managing arthritis pain for older adults. The study protocol had been registered in PROSPERO (International prospective register of systematic reviews). The registration number is CRD42019129716. Link: http://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42019129716 .